Problems Faced by English Teachers of Lower Secondary Schools in Assessments - nopita, dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
Dalam pengajaran Bahasa Inggris, guru memegang peranan penting dalam pencapaian tujuan pembelajaran. Kemampuan guru dalam merancang proses pembelajaran sangat berpengaruh terhadap tingkat pencapaian siswa. Agar dapat meengetahui tingkat capaian pembelajaran siswa, guru diharapkan untuk mempunyai kemampuan yang baik dalam merancang penilaian. Artikel ini bertujuan untuk memaparkan masalah-masalah yang dihadapi guru Sekolah Menengah Pertama (SMP) dalam merancang penilaian proses pembelajaran yang dilakukan oleh siswa, yang merupakan hasil penelitian. Adapun data penelitian diperoleh dari guru-guru Bahasa Inggris di SMPN 17 Bintan, SMPN 3 Bintan, SMPN 2 Bintan, dan SMPN 12 Bintan melalui pengamatan dan wawancara. Hasil penelitian menunjukkan bahwa guru-guru mata pelajaran Bahasa Inggris di Kabupaten Bintan benar-benar mengalami kesulitan dalam merancang penilaian terkait bentuk dan fokus penilaian. In the world of teaching English as a foreign language, teachers do hold a pivotal role in achieving the learning goals. The teachers’ skill in designing their classroom instruction contributes to students’ level of learning achievements. To be able to see the students’ achievement in learning, English teachers are required to have knowledge and skill in designing the assessment. This article, derived from a research result, intends to explore secondary school English language teachers’ problems related to English language assessment. There were 4 lower secondary schools in Bintan regency involved as the subjects of the research: SMPN 17 Bintan, SMPN 3 Bintan, SMPN 2 Bintan, and SMPN 12 Bintan. The instruments of the research were observation and interview. Finally, it was found that English language teachers of secondary schools in Bintan regency had serious problems in designing English language assessments related to the forms and the focus of the assessment. Keywords: Lower secondary school, English teachers, assessment